Seawater Corrosion of the Anodized A1050 Aluminum Plate for Heat Exchangers - Hirofumi Arima (Metals)
To confirm the suitability of aluminum for the heat transfer surfaces as a heat exchanger material for ocean thermal energy conversion, the seawater corrosion resistance of aluminum plates in a plate heat exchanger was experimentally investigated. In this study, four different surface shapes with chevron angles of 45° and 60° and different treatment types of A1050 aluminum heat transfer surfaces were processed into herringbone patterns. Additionally, the surfaces of the test plates were either anodized or untreated. In continuously flowing deep ocean water, the surface conditions of the test plates were observed at 1, 3, 6, and 12 months using mass measurements, visual inspection, laser microscopy, and SEM. For the anodized A1050 plates, regardless of the surface shape, there was almost no change in the mass, laser microscopy, or SEM results even after 12 months. In contrast, the untreated plate mass decreased in the samples after 3 months or later, and the mass reduction rate was approximately 2–7%. In conclusion, untreated aluminum is not suitable for use in seawater and an anodizing treatment is necessary for its use in heat exchangers for ocean thermal energy conversion.